2020
DOI: 10.1002/pchj.343
|View full text |Cite
|
Sign up to set email alerts
|

Moderating role of social support in the relationship between posttraumatic stress disorder and antisocial behavior in adolescents after the Ya'an earthquake

Abstract: This study explored whether social support moderated the relationship between various symptoms of posttraumatic stress disorder (PTSD) and antisocial behavior. Participants were 597 adolescents from two middle schools in Lushan county, China, an area severely affected by the Ya'an earthquake. All four symptom clusters of PTSD significantly and positively correlated with antisocial behavior. Of the PTSD symptoms, only social support played a significant moderating role in the effects of intrusion and avoidance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
(64 reference statements)
1
7
0
Order By: Relevance
“…Multivariate logistic regression analysis revealed that adolescents with low social support showed 4.2 times greater risk of depression symptoms and 3.2 times greater risk of anxiety symptoms than those with high social support. Notably, our results are in general agreement with prior studies that examined social support and mental health in adolescents [34,39,40], especially during a catastrophic stressor, such as a tornado [41] or earthquake [42]. These findings indicate that social support is a significant important protective factor for mental health among adolescents.…”
Section: Discussionsupporting
confidence: 92%
“…Multivariate logistic regression analysis revealed that adolescents with low social support showed 4.2 times greater risk of depression symptoms and 3.2 times greater risk of anxiety symptoms than those with high social support. Notably, our results are in general agreement with prior studies that examined social support and mental health in adolescents [34,39,40], especially during a catastrophic stressor, such as a tornado [41] or earthquake [42]. These findings indicate that social support is a significant important protective factor for mental health among adolescents.…”
Section: Discussionsupporting
confidence: 92%
“…Thirdly, another interesting finding is that social support did not moderate the direct effects of occupational stressors and three mental health symptoms. The buffer theory of social support reveal that the positive impact of social support in reducing psychological distress only occurs with perceived stress or distress ( Cohen and Wills, 1985 ; Wang et al, 2020 ). For instance, a study found that for breast cancer patients, the most painful groups benefited the most from social support, but those with less distress did not get much additional benefit from social support ( Mallinckrodt et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have demonstrated that social support is an essential protective factor for depressive symptoms (Rueger et al, 2016;Lei et al, 2018), it is still unclear under which conditions perceived social support works to this end. In particular, the buffering effect model suggests that the positive impact of social support in reducing psychological distress only occurs when under stress (Auerbach et al, 2011;Dumitrache et al, 2017;Wang et al, 2020). Indeed, when individuals encounter obstacles or experience negative emotions in their daily lives, they are more likely to ask significant others for support and comfort (Vélez et al, 2016); for example, Dumitrache et al (2017) discovered that social support buffers against the impact of negative perceived health status and life satisfaction in adults.…”
Section: Social Supportmentioning
confidence: 99%